Neurofascin (NF)155- and NF186-Specific T Cell Response in a Patient Developing a Central Pontocerebellar Demyelination after 10 Years of CIDP - Klehmet, Juliane; Staudt, Max; Diederich, Jan-Markus; Siebert, Eberhard; Meinl, Edgar; Harms, Lutz; Meisel, Andreas (Frontiers in Neurology, 2017)
Background Information and pathobiological understanding about central demyelinating manifestation in patients, who primarily suffer from chronic inflammatory demyelinating polyneuropathy (CIDP), are scarce. Methods IFN-γ-response as well as antibodies against the (para)nodal antigens neurofascin (NF)155 and NF 186 had been tested by Elispot assay and ELISA before clinical manifestation and at follow-up. Case description and results The patient described here developed a subacute brainstem syndrome more than 10 years after diagnosis of CIDP under low-dose maintenance treatment of intravenous immunoglobulins (IVIG). MRI revealed enhancing right-sided pontocerebellar lesion. CSF examination showed mild pleocytosis and elevated protein, and negative oligoclonal bands. Further diagnostics exclude differential diagnoses such as tuberculoma, sarcoidosis, or metastasis. Specific IFN-γ response against NF155 and NF186 as measured by Elispot assay was elevated before clinical manifestation. NF155 and NF186 antibodies were negative. Escalation of IVIG treatment at 2 g/kg BW followed by 1.4 g/kg BW led to clinical remission albeit to a new asymptomatic central lesion. Follow-up NF155 and NF186-Elispot turned negative. Conclusion The case reported here with a delayed central manifestation after an initially typical CIDP and NF155 and NF186 T cell responses does not resemble described cases of combined central and peripheral demyelination but may reflect a novel subtype within the great clinical heterogeneity of CIDP.